2021
DOI: 10.1016/j.cels.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the complete kinetics of coxsackievirus B3 reveals human determinants of host-cell feedback

Abstract: Modeling the complete kinetics of coxsackievirus B3 reveals human determinants of host-cell feedback Graphical abstract Highlights d A complete kinetic model of acute infection by the coxsackievirus B3 enterovirus d Enteroviral replication organelles accelerate biochemistry on membrane surfaces d Type I interferon exaggerates different enteroviral susceptibilities of host cells d A common polymorphism in MAVS alters host-cell susceptibility to coxsackievirus B3

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 121 publications
(152 reference statements)
0
30
0
Order By: Relevance
“…To identify cellular processes that are essential for explaining SARS-CoV-2 replication in our experimental system, we developed a model that was devoid of mechanistic details in contrast to previous ODE-models of RNA virus replication that included aspects as positive and negative RNA strands, virus particle formation or shuttling between cellular compartments (Binder et al, 2013;Aunins et al, 2018;Zitzmann et al, 2020;Lopacinski et al, 2021). Modeling showed that taking into account the inhibition of the transcription of anti-viral response genes by virus proteins was required to explain our experimental dataset.…”
Section: Discussionmentioning
confidence: 99%
“…To identify cellular processes that are essential for explaining SARS-CoV-2 replication in our experimental system, we developed a model that was devoid of mechanistic details in contrast to previous ODE-models of RNA virus replication that included aspects as positive and negative RNA strands, virus particle formation or shuttling between cellular compartments (Binder et al, 2013;Aunins et al, 2018;Zitzmann et al, 2020;Lopacinski et al, 2021). Modeling showed that taking into account the inhibition of the transcription of anti-viral response genes by virus proteins was required to explain our experimental dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The virus was propagated in HeLa cells. Viral titers were determined using the plaque assay [ 77 ]. SH-SY5Y cells were incubated with CVB3 at the 1 multiplicity of infection (MOI) in serum-free DMEM for 1 h and further incubated in DMEM supplemented with 10% FBS for 30 h. For primary neurons, cells were incubated with the indicated MOI of CVB3 in neuron culture medium for 24 h. In the in vivo model, 8- to 11- week-old male mice were infected by intraperitoneal (IP) injection with 1.0 × 10 6 plaque forming units (PFUs) of CVB3 in 100 μl of phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…However, most computational models have limited documentation and require knowledge of structured programming to operate. To overcome this barrier for non-computationalists, we developed a graphical user interface (GUI) version of a publicly available model of coxsackievirus B3 (CVB3) infection ( Lopacinski et al., 2021 ). CVB3 is a member of the Picornavirus family of non-enveloped, positive-strand RNA viruses.…”
Section: Before You Beginmentioning
confidence: 99%
“…The model simplifies some viral life cycle processes to improve interpretability and utility when performing in silico experiments. For complete details on the use and execution of this protocol, please refer to Lopacinski et al. (2021) .…”
mentioning
confidence: 99%
See 1 more Smart Citation